Environmental impacts of fireworks on aerosol characteristics and radiative properties over a mega city, India. (August 2020) - Chhabra, Abha; Turakhia, Tejas; Sharma, Som; Saha, Sourita; Iyer, Rajesh; Chauhan, Prakash
Abstract: The study focusses to investigate the variations in aerosol characteristics, concentrations and radiative properties due to the burning of firecrackers during Diwali festival event followed with New year festival celebrations over a representative urban environment. A six day's long intensive in situ measurements of Black Carbon, Particulate Matter and Aerosol Optical Depth were collected to capture pre to post-Diwali and New Year festival celebrations marked with massive fireworks. We observed an increase of 286%, 89.5%, and 60.5%, in BC, PM10, and PM2.5 concentrations, respectively on festival night as compared to pre-event days. An increase in in situ measured AOD is comparable with concurrent satellite derived AOD. Angstrom exponent, α > 1.0 along with high turbidity coefficient; β estimated for the festival period clearly implies the abundance of fine-mode particles, probably the smoke aerosols loading from fireworks. The Mie-scattered return signals received by the ground based Raman LiDAR at 532 nm showed an increased concentration of ' anthropogenic aerosols ', attributed to the increased crackers activity. Space based CALIPSO LiDAR observations also validate the presence of ' polluted dust ' and ' smoke ' types aerosols at the near surface to 5 km altitude over the study area. A sharp increase in gaseous air pollutants like SO2 and NOx concentrations exceeding the National Ambient Air Quality Standards is also observed. The COART model run simulations in SWIR region showed an increased 'cooling' at the surface (−125 Wm −2 to −185 Wm −2 ) as compared to 'warming' in the atmosphere during the event period. A maximum heating rate (1.9 Kday −1 ) due to total aerosol radiative forcing is also estimated. These investigations provide useful insights into the impact of burning firecrackers on urban air quality besides radiative impacts at a regional scale. Such celebration induced air pollution events may lead to severe health impacts; particularly respiratory and cardiovascular ailments in the resident population. Highlights: Variations in air pollutants concentrations, aerosol characteristics and radiative properties due to firecrackers burning. Comprehensive study built on in-situ data, ground and space LiDAR observations, satellite data, Radiative Forcing modelling. Advances our knowledge of air quality impacts of fire crackers burning practiced on several occasions across the countries. Strong insights into the impact of burning firecrackers on urban air quality besides radiative impacts at regional scale.